A place holder: the social sciences of monkeys and apes - Véronique Servais (Revue de Primatologie)
With the rise of cognitive sciences, the nature/culture debate has been reignited, and this debate often takes the form of a discussion about the opportunities and dangers of the naturalization of the social. Faced with what they perceive as a threat and an invasion of their discipline by the natural sciences, social science researchers often react by denying that natural sciences have any relevance for their own discipline, as though the biological and cultural aspects of human beings were separate entities, each one being a subject for individual study. This only serves to widen the gulf between two sister-disciplines, increases the polarization of the nature/culture duality and makes it even more difficult to connect the two. The point of view put forward in this paper shifts the emphasis of these discussions slightly. It does not take account of the contributions, whether desirable or not, made by natural sciences to sociology or anthropology, but rather argues in favor of a sociology of primates. By using examples drawn from cooperation studies, this paper aims to point to some problems that demonstrate the limitations of biological explanations for social behavior in primates. If we look beyond these limitations, there lies an unnamed world ripe for exploration by social science. This involves the invention of new methods and the definition of new objects (such as “affective cultures” for example) that appear to be composites of nature and culture. An empirical study of these composites would perhaps pave the way for a future understanding of the way in which biological and social determinants are woven into the reality of individual and collective histories. This would, in turn, make it possible to better identify the innate elements of the social skills of primates and to limit the importation of adaptationist theories into social sciences. In other words, the issue here is to replace an ideological debate with empirical questions. This paper is a revised version a paper previously published in SociologieS under the title : “Faut-il faire la sociologie des singes?”